Correction of inter‐scan motion artifacts in quantitative R1 mapping by accounting for receive coil sensitivity effects. Issue 5 (26th November 2015) - Papp, Daniel; Callaghan, Martina F.; Meyer, Heiko; Buckley, Craig; Weiskopf, Nikolaus
Abstract : Purpose: Inter‐scan motion causes differential receive field modulation between scans, leading to errors when they are combined to quantify MRI parameters. We present a robust and efficient method that accounts for inter‐scan motion by removing this modulation before parameter quantification. Theory and Methods: Five participants moved between two high‐resolution structural scans acquired with different flip angles. Before each high‐resolution scan, the effective relative sensitivity of the receive head coil was estimated by combining two rapid low‐resolution scans acquired receiving on each of the body and head coils. All data were co‐registered and sensitivity variations were removed from the high‐resolution scans by division with the effective relative sensitivity. R1 maps with and without this correction were calculated and compared against reference maps unaffected by inter‐scan motion. Results: Even after coregistration, inter‐scan motion significantly biased the R1 maps, leading to spurious variation in R1 in brain tissue and deviations with respect to a no‐motion reference. The proposed correction scheme reduced the error to within the typical scan–rescan error observed in datasets unaffected by motion. Conclusion: Inter‐scan motion negatively impacts the accuracy and precision of R1 mapping. We present a validated correction method that accounts for position‐specific receive field modulation. Magn Reson Med 76:1478–1485, 2016. © 2015 The Authors. Magnetic Resonance in Medicine published by Wiley Periodicals, Inc. on behalf of International Society for Magnetic Resonance in Medicine. This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.